Islam dan Akulturasi Budaya Lokal di Indonesia - Imam Wahyudin (LPPM IAIN Sorong, 2015)
There are many discouse between culture and religion, special in Indonesia country. Actually, relation each other can’t be different. In religion velue is universal. The culture is parcial. So the value of religion takes effect the local culcure. In Indonesia relation is very accommodative religion in culture and culture in religion. Manifesto of universal Islamic religion applies in culture of society. The value of Islam religion includes ettited of society. And, Culture includes the religion. The universal of religion include of aqidah, syariah, dan hakikah. This article tries to describe the problem